2007
DOI: 10.2353/ajpath.2007.061281
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Oxidant Stress and Extended Lifespan in Mice Exposed to a Low Glycotoxin Diet

Abstract: Aging is accompanied by increased oxidative stress (OS) and accumulation of advanced glycation end products (AGEs). AGE formation in food is temperature-regulated , and ingestion of nutrients prepared with excess heat promotes AGE formation , OS , and cardiovascular disease in mice. We hypothesized that sustained exposure to the high levels of pro-oxidant AGEs in normal diets (Reg AGE ) contributes to aging via an increased AGE load , which causes AGER1 dysregulation and depletion of antioxidant capacity , and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
180
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(198 citation statements)
references
References 64 publications
12
180
0
6
Order By: Relevance
“…Furthermore, one study found that reducing dietary exposure to preformed AGEs (achieved by reducing the exposure of the diet to heat during processing) extended both mean and maximum life span of mice (49). Even more intriguingly, a study of CR in rats reported reduced AGE accumulation in the animals with restricted food intake (50), and more recently, a study looking at the relationship between CR, AGE accumulation, and life span found that feeding mice a diet high in AGEs blocked CR's ability to extend mean or maximum life span (51).…”
Section: Advanced Glycation End Productsmentioning
confidence: 99%
“…Furthermore, one study found that reducing dietary exposure to preformed AGEs (achieved by reducing the exposure of the diet to heat during processing) extended both mean and maximum life span of mice (49). Even more intriguingly, a study of CR in rats reported reduced AGE accumulation in the animals with restricted food intake (50), and more recently, a study looking at the relationship between CR, AGE accumulation, and life span found that feeding mice a diet high in AGEs blocked CR's ability to extend mean or maximum life span (51).…”
Section: Advanced Glycation End Productsmentioning
confidence: 99%
“…Recent studies in mice have shown that decreased intake, or formation, of protein-AGEs can make major contributions to lifespan extension in mice (Cai et al, 2007;Uribarri et al, 2007a and2007b). MG, a spontaneously-generated glycolytic by-product, induces senescence in cultured fibroblasts (Sejersen and Rattan, 2008), and is a primary source of intracellular glycation in both yeast (Gomes et al, 2008) and mice (Morcos et al, 2008).…”
Section: Carnosine and Post-synthetic Protein Modificationmentioning
confidence: 99%
“…Furthermore, data obtained from humans and experimental animals indicate that exogenous food-ingested AGEs, present in highly thermolyzed fat-containing Westernized diets, result in elevated serum levels and increased tissue deposition of AGEs that can provoke the initiation or progression of insulin resistance and other endocrine abnormalities (Diamanti-Kandarakis et al 2007a, Cai et al 2008, de Assis et al 2009). Similarly, low-glycotoxin dietfed mice exhibit extended lifespan and reduced oxidative stress, while restriction of AGEs improves insulin resistance in T2DM patients (Cai et al 2007, Uribarri et al 2011.…”
Section: Introductionmentioning
confidence: 99%